Concentrations of Metals in Tissues of Cockle Anadara granosa (Linnaeus, 1758) from East Java Coast, Indonesia, and Potential Risks to Human Health - Agoes Soegianto; Trisnadi Widyaleksono Catur Putranto; Wahyuhani Lutfi; Firdha Nur Almirani; Arfian Rahmat Hidayat; Andi Muhammad; Rachmadiva Aulia Firdaus; Yaniar Sari Rahmadhani; Desi Aina Nur Fadila; Dewi Hidayati (International Journal of Food Science)
This study reports the presence of Cd, Pb, Zn, Hg, Cu, and Cr in the cockles (Anadara granosa, Linnaeus, 1758) harvested along the East Java Coast, Indonesia. The concentrations of metals were determined by atomic absorption spectrometer and expressed in mg kg-1 wet weight. The concentrations of metals ranged from 0.11 to 0.82 mg kg−1 for Cd, 0.10 to 0.54 mg kg−1 for Pb, 10.22 to 19.04 mg kg−1 for Zn, 0.02 to 1.47 mg kg−1 for Hg, 1.79 to 4.76 mg kg−1 for Cu, and 1.64 to 3.79 mg kg−1 for Cr. The metal concentrations in the whole tissues of cockles were in the order Zn>Cu>Cr>Hg>Cd>Pb. The Cd and Pb levels in cockles were found to be higher than the permissible limit for human consumption according to EC and FAO; the levels of Hg exceeded the EC, Hong Kong, Australia, and Indonesia standards; and the levels of Cr exceeded the Hong Kong standard. The estimated weekly intake (EWI) of cockles indicates that the concentrations of Cd and Hg in the cockle tissues from Gresik were higher than the provisional tolerable weekly intake (PTWI); meanwhile, the concentrations of Cr of cockles from all locations were higher than and close to the PTWI. The THQ values for Cd at Gresik, for Hg at Gresik, Surabaya, and Pasuruan, and for Cr at all locations were higher than one indicating that these metals pose potential noncarcinogenic effects to consumers. Reducing the consumption of cockles should be done in order to minimize the adverse effects of metals especially Cd, Hg, and Cr to human health.